Safety and Tolerance of Radical Hysterectomy for Cervical Cancer in the Elderly - George, Erin M. (2014)
BACKGROUND: Despite institutional studies that suggest that radical hysterectomy for cervical cancer is well tolerated in the elderly, little population-level data is available on the procedure’s outcomes in older women. We performed a population-based analysis to determine the morbidity, mortality, and resource utilization of radical hysterectomy in elderly women with cervical cancer. METHODS: Patients recorded in the Nationwide Inpatient Sample with invasive cervical cancer who underwent abdominal radical hysterectomy between 1998–2010 were analyzed. Patients were stratified by age: <50, 50–59, 60–69, and ≥70 years. We examined the association between age and the outcomes of interest using chi square tests and multivariable generalized estimating equations. RESULTS: A total of 8199 women were identified, including 768 (9.4%) women age 60–69 and 462 (5.6%) women ≥70 years of age. All cause morbidity increased from 22.1% in women <50, to 24.7% in those 50–59 years, 31.4% in patients 60–69 years and 34.9% in women >70 years of age (P<0.0001). Compared to women < 50, those >70 were more likely to have intraoperative complications (4.8% vs. 9.1%, P=0.0003), surgical site complications (10.9% vs. 17.5%, P<0.0001), and medical complications (9.9% vs. 19.5%, P<0.0001). The risk of non-routine discharge (to a nursing facility) was 0.5% in women <50 vs.12.3% in women ≥70 (P<0.0001). Perioperative mortality women ≥70 years of age was 30 times greater than that of women <50 (P<0.0001) CONCLUSION: Perioperative morbidity and mortality are substantially greater in elderly women who undergo radical hysterectomy for cervical cancer. Non-surgical treatments should be considered in these patients.